Clinical Characteristics Of Patients With Nasopharyngeal Carcinoma - Radiana Syamsu; Andi Baso Sulaiman; Renato Vivaldi Kuhuwael (Jurnal EduHealth, 2024)
Nasopharyngeal carcinoma (NPC) is a malignant tumor that grows in the nasopharyngeal region with predictions of Rosenmuller's fossa and nasopharyngeal roof. The incidence of nasopharyngeal cancer in Indonesia is about 5.6 cases per 100,000 population where the discovery of new cases is 15,000 per year. The etiology of nasopharyngeal cancer is multifactorial including Epstein Barr virus (EBV) infection. Treatment of nasopharyngeal carcinoma is complex due to its proximity to critical structures. This research is a Literature Review research with Narrative Review design. This method is used to identify, review, evaluate, and interpret all available research. Characteristics of nasopharyngeal carcinoma patients are that men are the gender most commonly affected by NPC, with the age of 46-55 years being the most vulnerable age, the most common symptoms in patients with NPC are nasal congestion with lumps in the neck, the most The clinical stage of NPC patients is stage IVA, while the most histopathological picture of NPC is the type of Non-Keratinizing Squamous Cell Carcinoma undifferentiated. Based on several journals above regarding the clinical characteristics of patients with nasopharyngeal carcinoma, it can be concluded that men are the gender that most often experiences nasopharyngeal carcinoma in several studies that have been mentioned. While the age that is susceptible to nasopharyngeal carcinoma is 46-55 years. The most common symptoms in patients with nasopharyngeal carcinoma are nasal congestion with lumps in the neck. The most clinical stage of patients is stage IVA. While the histopathology of nasopharyngeal carcinoma is the type of Non-Keratinizing Squamous Cell Carcinoma undifferentiated.